Does Muscle Strength Change Over Time in Patients With Hypermobile Ehlers‐Danlos Syndrome/Hypermobility Spectrum Disorder? An Eight‐Year Follow‐Up Study. Issue 7 (18th June 2021) - Coussens, Marie; Calders, Patrick; Lapauw, Bruno; Celie, Bert; Banica, Thiberiu; De Wandele, Inge; Pacey, Verity; Malfait, Fransiska; Rombaut, Lies
Abstract : Objective: Reduced maximal muscle strength and strength endurance have been found in patients with hypermobile Ehlers‐Danlos syndrome/hypermobility spectrum disorder (hEDS/HSD) and are recognized as common associated features of the disorder. However, the extent to which these parameters change over time is currently not documented. Therefore, the purpose of this 8‐year follow‐up study was to investigate this evolution. Methods: Thirty female patients (mean age 41 years) with hEDS/HSD and 17 controls participated at baseline and 8 years later. Maximal muscle strength and strength endurance tests of the knee flexors and extensors, and 2 lower‐extremity posture maintenance tests were performed to evaluate static strength endurance. In addition, muscle mass and density were evaluated by dual‐energy x‐ray absorptiometry and peripheral quantitative computed tomography. Results: Maximal muscle strength and strength endurance were significantly lower at both baseline and follow‐up in the hEDS/HSD group compared to the control group ( P ≤ 0.007). Maximal muscle strength of the knee flexors (decreased in the control group: pɳ 2 = 0.139), strength endurance of the knee extensors (decreased in the hEDS/HSD group and increased in the control group: pɳ 2 = 0.244), and muscle density (decreased in the hEDS/HSD group: pɳ 2 = 0.263) showed a significantly different evolution over 8 years. No other significant differences in evolution were found. Conclusion: Decreased muscle strength was identified at both time points in patients with hEDS/HSD. The evolution of most muscle strength parameters over time did not significantly differ between groups. Future studies should focus on the effectiveness of different types of muscle training strategies in hEDS/HSD patients.